Sujets de l’amour. Formes de la représentation de soi dans la société du cours d’après „Le Favori“ - Steigerwald, Jörn (Mme de Villedieu et le théâtre. Actes du colloque de Lyon (11 et 12 septembre 2008))

Von der (Un-)Möglichkeit sozialer Praxis im Theaterstaat von Louis XIV: Madeleine de Scudérys dialogische Inszenierung von Festbeschreibungen - Steigerwald, Jörn (Soziale und ästhetische Praxis der höfischen Fest-Kultur im 16. und 17. Jahrhundert)

Galanterie als Kristallisations- und Kreuzungspunkt um 1700: Eine Problemskizze - Steigerwald, Jörn (Kleine Schriften des IZEA 1, 2009. Galanterie und Frühaufklärung)

Soziale und ästhetische Praxis der höfischen Fest-Kultur: Eine Problemskizze - Steigerwald, Jörn (Soziale und ästhetische Praxis der höfischen Fest-Kultur im 16. und 17. Jahrhundert)

Les arts et l’amour galant: à propos de „La Promenade de Versailles“ de Madeleine de Scudéry - Steigerwald, Jörn (Littératures classiques 2009 / 3, Les Discours artistiques de l'amour à l'âge clas- sique. Sous la direction de Kirsten Dickhaut / Alain Viala)

Konzessive Konstruktionen. Ein Verfahren zur Rekonstruktion von Konzessionen - Rezat, Sara (Zeitschrift für Germanistische Linguistik 37)

Feasibility of free space quantum key distribution with coherent polarization states - Elser, D.; Bartley, Tim; Heim, B.; Wittmann, Ch; Sych, D.; Leuchs, G. (New Journal of Physics)
We demonstrate for the first time the feasibility of free space quantum key distribution with continuous variables under real atmospheric conditions. More specifically, we transmit coherent polarization states over a 100 m free space channel on the roof of our institute's building. In our scheme, signal and local oscillator (LO) are combined in a single spatial mode, which auto-compensates atmospheric fluctuations and results in an excellent interference. Furthermore, the LO acts as a spatial and spectral filter, thus allowing unrestrained daylight operation.

Sprache und Interaktion im Kindergarten. Eine quantitativ-qualitative Analyse der sprachlichen und kommunikativen Kompetenzen von drei- bis sechsjährigen Kindern - Albers, Timm

Wenn Wörter auf Wanderschaft gehen .... Aspekte kultureller, nationaler und geschlechtsspezifischer Differenzen in deutschsprachiger Migrationsliteratur - Zierau, Cornelia

„Ohne Deutsch kann man hier nichts machen“ – Förderung von Schüler(-innen) mit Migrationshintergrund - Zierau, Cornelia (Deutschmagazin 2/2009)

Accurate RTOS Modelling and Analysis with SystemC - Zabel, Henning; Müller, Wolfgang; Gerstlauer, Andreas (Hardware Dependent Software - Principles and Practice)
Today, mobile and embedded real-time systems have to cope with the migration and allocation of multiple software tasks running on top of a real-time operating system (RTOS) residing on one or several system processors. Each RTOS has to be configured towards the individual needs of the application and environment. For this, different scheduling strategies and task priorities have to be evaluated in order to keep execution and response times for a given task set. Abstract RTOS simulation is applied to analyze different parameters in early design phases. This chapter presents a SystemC RTOS library for abstract yet accurate RTOS sim- ulation, supporting modeling of preemption in the presence of prioritized and nested interrupts. After introducing basic principles of abstract RTOS simula- tion, we present our SystemC library in detail. Thereafter, we discuss related approaches and close with applications in electronic automotive systems design and some evaluations.
Keywords: RTOS Modelling; RTOS Simulation; SystemC; Task Scheduling; Interrupt Analysis

Hardware-dependent Software - Introduction and Overview - Ecker, Wolfgang; Müller, Wolfgang; Dömer, Rainer (Hardware Dependent Software - Principles and Practice)
Rapidly rising system complexity has created a growing productivity gap in the design of electronic systems. One critical component is Hardware-dependent Software (HdS), the importance of which is often underestimated. In this chap- ter, we introduce HdS and illustrate its role in the overall system design context. We also provide a brief overview and define a basic HdS terminology and con- clude with a brief outlook over the following chapters in this book.
Keywords: Hardware-dependent Software; Systems Complexity; Productivity Gap

Jana Hrdličková: Es sieht schlimm aus in der Welt. Der moralische Appell in den Hörspielen von Marie Luise Kaschnitz - Famula, Marta (Brünner Beiträge zur Germanistik und Nordistik, 14 (2009) H. 1–2)

Gleichnisse des erkenntnistheoretischen Scheiterns. Thomas Glavinics Roman Die Arbeit der Nacht in der Tradition des labyrinthischen Erzählens bei Franz Kafka und Friedrich Dürrenmatt - Famula, Marta (Transitträume. Beiträge zur deutschsprachigen Gegenwartsliteratur (Germanistik und Gegenwartsliteratur 4))

Ermittlung der Verluste von Schneckengetrieben mit ZK-Schnecke - Magyar, Balázs; Horák, P (GÉP)

Übergang Förderschule-Beruf: Neue Wege der Gestaltung - Heger, M-; Laubenstein, Désirée (In: Impulse Nr. 4)

Sprachwandel

Das Niederdeutsche in der Sprachgeschichtsschreibung - Tophinke, Doris (Korrespondenzblatt des Vereins für Niederdeutsche Sprachforschung)

Vom Vorlesetext zum Lesetext: Zur Syntax mittelniederdeutscher Rechtsverordnungen im Spätmittelalter - Tophinke, Doris (Oberfläche und Performanz. Untersuchungen zur Sprache als dynamische Gestalt)

Wirklichkeitserzählungen im Internet - Tophinke, Doris (Wirklichkeitserzählungen. Felder, Formen und Funktionen des nicht-literarischen Erzählens)